Response of ginger (Zingiber officinale) to methods of planting and levels of phosphorus in a rehabilitated forest developed on sodie land - Pushpendra Singh, Ajai Singh, Bajrang Singh, Achal Singh, (Journal of Spices and Aromatic Crops, 2003)
Experiments were conducted during 1999 and 2000 at Banthra Research Station of NBRI, Lucknow (UP) to standardize agro-techniques of ginger cultivation in forest gaps. The response of three lnethods of planting and three levels of phosphorus was studied, which revealed that the flat bed followed by earthing and application of P 205 50 kg ha-1 recorded the maximum growth and yield (7.88 t ha-1). These treatments also influenced the bio-chemical composition positively showing greatest values of crude protein (9%), crude fibre (5.15%) and volatile oil (1.45%). The study showed a modest potential of ginger cultivation in a semi-reclaimed sodic soils through afforestations.